RF Communication and RSSI Based Location Detection with Trilateration Method - Cetin, Aml; Isikli, Ertugrul; Turk, Ahmet Serdar (IEEE, 2024)
In this study, a location determination algorithm has been developed specifically for local use due to the potential unavailability of GNSS systems, which are satellite-based systems, in various war, disaster, and crisis situations. In order to mitigate the risk of GNSS systems becoming unavailable during war, disaster, and crisis situations, a location determination algorithm has been developed by particularly utilizing the trilateration method (Circle Intersection Method) working in local areas, combining RSSI (Received Signal Strength Indicator) parameters. In the research, a TTGO LoRa32 device containing an SX1278 LoRa module and ESP-32 microcontroller, operating in 4 frequency bands of 868/915 MHz, has been used as the communication module and microcontroller. In tests and measurements conducted in a 25000 m2 area, an average accuracy of about 14 meters has been achieved. Increases in the accuracy of location determination have been observed through optimization of system parameters considering channel conditions and simple error correction methods.
Keywords: RSSI; GNSS; Trilateration; Location Detection; WLAN; Computer Science; Engineering; Telecommunications